Idiopathic Bilateral Bloody Tearing - Emrullah Beyazyıldız; Yasemin Özdamar; Özlem Beyazyıldız; Hasan Yerli (Case Reports in Ophthalmological Medicine)
Bloody tear is a rare and distinct clinic phenomenon. We report a case presenting with the complaint of recurrent episodes of bilateral bloody tearing. A 16-year-old girl presented to our clinic with complaint of bloody tearing in both eyes for 3 months. Bloody tearing was not associated with her menses. A blood-stained discharge from the punctum was not observed during the compression of both nasolacrimal ducts. Nasolacrimal passage was not obstructed. Imaging studies such as dacryocystography and gradient-echo magnetic resonance imaging (MRI) of nasolacrimal canal were normal. Intranasal endoscopic evaluation was normal. We collected samples from bloody tears two times and pathological examination was performed. Pathological analysis showed lots of squamous cells and no endometrial cells; dysplastic cells were found. Further evaluations for underlying causes were unremarkable. No abnormalities were found in ophthalmologic, radiologic, and pathologic investigations. This condition is likely a rare abnormality and the least recognized aetiology for the idiopathic phenomenon.